2017
DOI: 10.3892/etm.2017.4467
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins from black rice (Oryza sativa) promote immune responses in leukemia through enhancing phagocytosis of macrophages in vivo

Abstract: Rice is a staple food in numerous countries around the world. Anthocyanins found in black rice have been reported to reduce the risk of certain diseases, but the effects of crude extract of anthocyanins from Asia University-selected purple glutinous indica rice (AUPGA) on immune responses have not yet been demonstrated. The current study aimed to investigate whether AUPGA treatment could affect immune responses in murine leukemia cells in vivo. Murine acute myelomonocytic leukemia WEHI-3 cells were intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Institute (Hsinchu, Taiwan, ROC). Cells were cultured with IMDM supplemented with 10% FBS, 2 mM L-glutamine and antibiotics (100 units/ml penicillin, 100 μg/ml streptomycin) in 75 cm 2 tissue culture flasks and placed at 37˚C in a humidified atmosphere of 5% CO 2 (21).…”
Section: Wehi-3 Cells Murine Acute Myelomonocytic Leukemia Wehi-3 Cementioning
confidence: 99%
See 3 more Smart Citations
“…Institute (Hsinchu, Taiwan, ROC). Cells were cultured with IMDM supplemented with 10% FBS, 2 mM L-glutamine and antibiotics (100 units/ml penicillin, 100 μg/ml streptomycin) in 75 cm 2 tissue culture flasks and placed at 37˚C in a humidified atmosphere of 5% CO 2 (21).…”
Section: Wehi-3 Cells Murine Acute Myelomonocytic Leukemia Wehi-3 Cementioning
confidence: 99%
“…Group II mice received normal diet as positive control; group III, IV and V mice received laminarin at 1, 2.5 and 5 mg/ml with ddH 2 O, respectively, by oral gavage every 2 days for 14 days (total of seven times). All animals were individually weighed during the oral treatment, and at the end of treatment, all mice were weighed and sacrificed as described previously (21).…”
Section: Wehi-3 Cells Murine Acute Myelomonocytic Leukemia Wehi-3 Cementioning
confidence: 99%
See 2 more Smart Citations
“…Results indicated that laminarin reduced NK cell cytotoxic activity at a target ratio of 50:1. Use of Yac-1 cells as a target cells for examining NK cell cytotoxic activity measurement is well documented (15).…”
Section: Discussionmentioning
confidence: 99%